2008
DOI: 10.1159/000151351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plateletpheresis on the Fenwal Amicus and Fresenius Com.Tec Cell Separators

Abstract: Background: A variety of apheresis devices are now available on the market for plateletapheresis. We compared two apheresis instruments (Fenwal Amicus and Fresenius COM.TEC) with regard to processing time, platelet (PLT) yield and efficiency, and white blood cell (WBC) content. Material and Methods: Donors undergoing plateletpheresis were randomly separated into two groups (either the Amicus or the COM.TEC cell separator). Results: In the pre-apheresis setting, 32 plateletpheresis procedures performed with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Again, our CE results with Trima results (64.94 ± 7.33%) were lower than the reported average of 75.9 ± 9.7% . There is little data concerning plateletpheresis with the COM.TEC device . Altuntas et al reported a blood volume processed was higher in the COM.TEC compared with the Amicus (3,481 vs. 2,850 mL; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Again, our CE results with Trima results (64.94 ± 7.33%) were lower than the reported average of 75.9 ± 9.7% . There is little data concerning plateletpheresis with the COM.TEC device . Altuntas et al reported a blood volume processed was higher in the COM.TEC compared with the Amicus (3,481 vs. 2,850 mL; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Several publications reported on this subject [1][2][3][4][5][6][7][8][9][10][11][12][13]. The reactivity of PLT in the recipient of the PC can only be estimated by the recovery of the hemostatic balance.…”
Section: Introductionmentioning
confidence: 99%
“…The MCS+ is being used with the advantage of easy operation and high reliability. Many studies have been made to assess different available apheresis machines regarding procedure time, platelet yield, product quality, adverse effects and other variables (Patel et al , ; Ranganathan, ; Altuntas et al , ; Tendulkar & Rajadhyaksha, ). For example, one study showed that MCS+ could produce almost the same amount of CD34+ compared with the Cosmic Backgoround Explorer (COBE) method, whereas the latter showed more potential (Rock & Sutton, ).…”
mentioning
confidence: 99%